Labor Supply of Married Women in Canada, 1995 - zhao, Bin (Université d'Ottawa | University of Ottawa, 2005)
Based on the data from the 1996 Census for Canada, this study examines the labor supply behavior of married women in Canada. To eliminate the inherent selection bias, Heckman's sample selection bias procedure is employed in the wage rate and hours of work